Pengaruh Penggunaan Handphone terhadap Konsentrasi dan Hasil Belajar Siswa SMKS Muhammadiyah 9 Medan - Muhammad Diaz Rizki; Nadlrah Naimi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The use of mobile phones among students has increased significantly in line with the rapid development of information and communication technology. This phenomenon provides positive impacts in terms of easier access to information and learning resources, but it also brings negative consequences such as distractions that may reduce students’ learning concentration. This study aims to investigate the influence of mobile phone usage on students’ concentration and learning outcomes at vocational high schools. A quantitative approach with a correlational design was employed, involving 60 respondents from twelfth-grade students selected through purposive sampling. The research instruments consisted of a questionnaire measuring the intensity and patterns of mobile phone usage, as well as a learning achievement test to assess students’ academic performance. Data were analyzed using multiple linear regression to determine both partial and simultaneous relationships among variables. The results indicate that mobile phone usage has a significant influence on learning concentration, which subsequently affects students’ academic performance. The findings show that higher intensity of mobile phone use for non-academic activities, such as social media, gaming, and online entertainment, tends to decrease students’ focus, thereby lowering their academic achievement. Conversely, the use of mobile phones for academic purposes, such as searching for references, accessing learning materials, and communicating in study groups, can support the learning process. Thus, mobile phones play a dual role, functioning either as a facilitator or as a barrier to learning, depending on the usage patterns.